Monitoring water content of rat lung tissuein vivo using microwave reflectometry - Schäfer, Michael; Nowak, K.; Kherad, B.; Gross, W.; Post, Stefan; Gebhard, Martha-Maria (Medical & biological engineering & computing, 2004)
Measurement of lung water is an important diagnostic means of assessing pulmonary oedema. Water content affects the dielectric spectrum at microwave frequencies, but quantification is still a problem. A new lung tissue model is presented that allows the calculation of water content from dielectric permitivity. The dielectric permitivity of lung tissue was measured by microwave reflectometry using a noninvasine surface probe. During perfusion of rat lungs (n=22) with blood, injury was induced by interruption of the blood supply for a duration between 0 (control) and 2h. Water content was assessed from dielectric permitivity using a new mixture formula and was also determined by drying and weighing. The mixture formula allows for the dielectric polarisation of water, dry matter and air in the tissue. A linear correlation was found between total water content determined from dielectric permitivity and that from drying and weighing (y=1.001x, R2=0.8). Lung injury showed an increase in total water content from 80.9±1.2% (control) to 84.1±0.9% (p<0.01). The analysis of dielectric permitivity data at microwave frequencies with the new tissue model is sensitive enough to detect water accumulation produced by lung injury and it can be used to monitor total water content without tissue destruction.
Gesehen am 31.05.2022